The absolute recommendation of chamber Neubauer method for platelets counting instead of indirect methods in severe thrombocytopenic patients - Oliveira Raimundo Antônio Gomes; Takadachi Maria Mariko; Nonoyama Kimiyo; Barretto Orlando Cesar de Oliveira (Sociedade Brasileira de Patologia Clínica, 2003)
Accurate and precise platelet counting is crucial for recommending platelets transfusion for thrombocytopenic patients, principally when platelet counts are bellow 30,000/µl. As most laboratories still use the indirect methods for confirming low automated platelet counts, this work compared two indirect methods used in practice (Fonio and Nosanchunk et al.) with the International Committee for Standardization in Hematology recommended direct method (Brecher and Cronkite). The obtained data show that the indirect methods present low precision and accuracy, and that the direct method should always be employed in severe thrombocytopenic samples thanks to its high precision.